Heat shock protein 27 is associated with freedom from graft vasculopathy after human cardiac transplantation. - De Souza, A; Wait, R; Mitchell, A; Banner, N; Dunn, M; Rose, M (2005)
Experimental studies have suggested that protective genes protect allografts from cardiac allograft vasculopathy (CAV), the major complication after cardiac transplantation. Here we have sought to confirm this hypothesis using long-term heart transplant recipients. Twenty-two patients that were 9 years or older after transplant were investigated; 11 of these were without angiographic evidence of CAV; 11 had developed early CAV at 1 to 3 years after transplant. To identify proteins that may act as protectors from CAV, a global proteomic approach was used comparing cardiac biopsies from 12 patients taken within the first 2 weeks after transplant and those taken after 9 years from the same patient. Proteins were separated by 2-D gel-electrophoresis, detected by silver staining, and analyzed using Progenesis software. A particular protein spot was found in 4/6 biopsies from patients without CAV, but absent from 5/6 biopsies from those with CAV (P=0.24); however, quantitative analysis of spot intensity showed a significant difference (0.061+/-0.05 versus 0.003+/-0.01, P=0.04). This spot was identified by mass spectrometry and a combination of techniques as a diphosphorylated form of HSP27. Immunohistochemistry of further biopsies not only validated that HSP27 was more abundantly expressed on biopsies without CAV but also showed it to be localized to blood vessels. In contrast, vessels from patients with CAV did not express HSP27 (P=0.028x10(-4)). Immunohistochemistry of 12 further early biopsies and nontransplanted heart showed HSP27 to be present in normal blood vessels. These findings suggest that expression of a specific diphosphorylated form of HSP27 is associated with healthy blood vessels; it appears to be lost from vessels of patients with graft vasculopathy.